2023
DOI: 10.1017/jfm.2023.126
|View full text |Cite
|
Sign up to set email alerts
|

Cargo carrying with an inertial squirmer in a Newtonian fluid

Abstract: We numerically investigate the hydrodynamics of a spherical swimmer carrying a rigid cargo in a Newtonian fluid. This swimmer model, a ‘squirmer’, which is self-propelled by generating tangential surface waves, is simulated by a direct-forcing fictitious domain method (DF-FDM). We consider the effects of swimming Reynolds numbers (Re) (based on the radius and the swimming speed of the squirmers), the assembly models (related to the cargo shapes, the relative distances (ds) and positions between the squirmer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…These dimensions have shown to be convergent when calculating the locomotion of a squirmer carrying a spherical cargo (Ouyang et al. 2023). The swimming Reynolds is set to Re = 0.01 at which the effects of the inertia on the swimming speed can be neglected (Wang & Ardekani 2012).…”
Section: Validation Of a Squirmer Through Giesekus Fluidsmentioning
confidence: 99%
“…These dimensions have shown to be convergent when calculating the locomotion of a squirmer carrying a spherical cargo (Ouyang et al. 2023). The swimming Reynolds is set to Re = 0.01 at which the effects of the inertia on the swimming speed can be neglected (Wang & Ardekani 2012).…”
Section: Validation Of a Squirmer Through Giesekus Fluidsmentioning
confidence: 99%
“…Boundary element numerical methods are employed to investigate swimming with increased deformation amplitudes, specifically concerning power efficiency and swimming performance. [29] Ouyang et al [30] assessed the influence of swimming Reynolds numbers and as-sembly models on assembly locomotion (where the squirmer and cargo are fixed together). The pusher-cargo model swims faster than other models at a finite Reynolds number and proves to be more efficient, with larger relative distances resulting in smaller carrying hydrodynamic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the puller-cargo model is more stable than the cargopuller model, and a larger distance leads to more unstable swimming. [30] Nie et al [31] and Ying et al [32] studied the movements and interactions of circular squirmers under gravity in a two-dimensional (2D) channel with finite fluid inertia and five typical locomotive modes were obtained. They found that pullers with higher pressure regions on their lateral sides are more prone to breakdown and stability loss.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better study microbial motions, Lighthill (1952) and Blake (1971) proposed the classical squirmer model to simulate microbial motions and it has been largely adopted in numerical and theoretical studies (Ishimoto and Gaffney 2013, Qi et al 2020, Aymen et al 2023, Ouyang et al 2023. In nature, microorganisms cannot exist in a completely infinite, unbounded region; as such, the boundary and geometry of the flow field can have a significant effect on the motion of microorganisms.…”
Section: Introductionmentioning
confidence: 99%